2020
DOI: 10.1113/jp280679
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sex on the age‐related adaptations of neuromuscular function and motor unit properties in elite masters athletes

Abstract: Masters athletes maintain high levels of activity into older age and allow an examination of the effects of aging dissociated from the effects of increased sedentary behaviour. r Evidence suggests masters athletes are more successful at motor unit remodelling, the reinnervation of denervated fibres acting to preserve muscle fibre number, but little data are available in females. r Here we used intramuscular electromyography to demonstrate that motor units sampled from the tibialis anterior show indications of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
48
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 63 publications
(141 reference statements)
0
48
1
Order By: Relevance
“…Electromyography (EMG), the recording of electrical activity from muscle ( Mills, 2005 ), is widely accepted and used to study MU structure and function ( Heckman and Enoka, 2012 ; Piasecki et al, 2018a ; Piasecki et al, 2020 ). These methods range in complexity but largely involve surface based and/or intramuscular measures, able to generate representations of the ionic exchange across the muscle fibre membrane.…”
Section: Neural Plasticity and Nmesmentioning
confidence: 99%
“…Electromyography (EMG), the recording of electrical activity from muscle ( Mills, 2005 ), is widely accepted and used to study MU structure and function ( Heckman and Enoka, 2012 ; Piasecki et al, 2018a ; Piasecki et al, 2020 ). These methods range in complexity but largely involve surface based and/or intramuscular measures, able to generate representations of the ionic exchange across the muscle fibre membrane.…”
Section: Neural Plasticity and Nmesmentioning
confidence: 99%
“…Several previous studies (Allen et al 2015;Hourigan et al 2015;Piasecki et al 2016bPiasecki et al , 2016aPiasecki et al , 2020Power et al 2016;Gilmore et al 2017; have incorporated NFEMG parameters to demonstrate the effects of specific diseases or ageing on individual MUs. The focus of this paper is to utilise MUPs and NFMs extracted from simulated EMG signals and those obtained from human muscles to explicitly describe and evaluate a range of NFEMG methods and parameters used to investigate neuromuscular alterations, including a new measure of NMJ instability, NFM segment jitter.…”
Section: Introductionmentioning
confidence: 99%
“…Although age‐ and inactivity‐related declines in neuromuscular function are known, in this issue of The Journal of Physiology , Piasecki et al . (2021) report the age‐related trajectory of neuromuscular function and motor unit adaptations in the tibialis anterior of both male and female masters athletes aged 44–88 years. Using intramuscular electromyography (EMG), they demonstrate a steady age‐related decline in muscle function (maximal torque and balance) and evidence of neuromuscular instability in both sexes.…”
mentioning
confidence: 99%
“…Moreover, Piasecki et al . (2021) examined neuromuscular function at 25% of maximal isometric voluntary contraction. Previous work has demonstrated that age‐related differences in motor unit firing rate increase with contraction intensity (Kamen & Knight, 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation